Controlled Release of Hydrophilic Active Agent from Textile Using Crosslinked Polyvinyl Alcohol Coatings - Limor Mizrahi; Rotem Kelman; Efrat Shtriker; David Meridor; Dror Cohen; Meital Portugal-Cohen; Elizabeth Amir (Journal of Functional Biomaterials)
Functional fabrics embedded with active materials that can be released in a controlled manner upon external triggering have been explored for biomedical and cosmetic applications. This study introduces a method for the fabrication of nonwoven fabrics coated with crosslinked polyvinyl alcohol (PVA) for in situ encapsulation and controlled release of hydrophilic active agent, allantoin. Two types of crosslinked coatings were examined using citric acid (CA) or polyacrylic acid (PAA) as crosslinkers. Based on gel content, differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) analyses PVA:CA coatings exhibited a higher crosslinking density compared to PVA:PAA systems. Swelling behavior was measured at 62% after 30 min for PVA:PAA 7:3 films and 36% after 60 min for PVA:CA 7:3 crosslinked films. The release of allantoin from the coated fabrics was influenced by the coating thickness (250–330 µm), the formulation viscosity (8–250 cP), allantoin content (1.2–4.2 mg) and the molecular weight between crosslinks (MC) 1,000,000–494 g/mol. PVA:CA 7:3 coating allowed the controlled release of 97% allantoin over 8 h, whereas PVA:PAA 7:3 coating exhibited a more prolonged release profile, with 96% of allantoin released over 20 h. Kinetic analyses of the release profiles revealed a good agreement with zero-order release.